Molecular and in silico evidences explain the anti-inflammatory effect of Trachyspermum ammi essential oil in lipopolysaccharide induced macrophages. (September 2020) - Bahuguna, Ashutosh; Ramalingam, Srinivasan; Arumugam, Aruna; Natarajan, Devarajan; Kim, Myunghee
Graphical abstract: Highlights: Anti-inflammatory role of Trachyspermum ammi essential oil (TAEO). TAEO lower lipopolysaccharide induced nitric oxide synthesis in macrophages. TAEO downregulates inducible nitric oxide synthase & hem oxygenase-1expression. A cyclooxygenase-2 inhibition activity ( in vitro & in silico ) displayed by TAEO. Abstract: This study presents the anti-inflammatory potential of Trachyspermum ammi essential oil (TAEO) against Escherichia coli lipopolysaccharide (LPS)-induced inflammation in RAW 264.7 macrophages. TAEO displayed the anti-inflammatory activity by reducing nitric oxide production and impact on the expression of nitric oxide synthases (iNOS), cyclooxygenase-2 (COX-2), and heme oxygenase-1 (HO-1). Besides, TAEO effectively inhibited the COX-2 enzyme activity with IC50 value at 4.49 μg/mL. Furthermore, the molecular docking and simulation studies suggest a strong interaction between COX-2 and the important TAEO components thymol, (-5.88 kcal/mol) and carvacrol (-6.30 kcal/mol). The thymol and carvacrol docked complexes are stabilized by hydrogen bonds (at alanine 188 and tyrosine 371) and several hydrophobic interactions at phenylalanine 196, tyrosine 371, tryptophan 373, and leucine 376 and alanine 185, alanine 188, phenylalanine 196, tryptophan 373, leucine 376, and leucine 377, respectively. These results collectively suggest the anti-inflammatory role of TAEO.